2002
DOI: 10.1124/jpet.302.1.188
|View full text |Cite
|
Sign up to set email alerts
|

Profound Spinal Tolerance after Repeated Exposure to a Highly Selective μ-Opioid Peptide Agonist: Role of δ-Opioid Receptors

Abstract: Recent studies suggest that ␦-opioid receptors play a role in the development of opioid tolerance and led us to hypothesize that highly selective -opioid agonists may produce less tolerance.]DALDA) has extraordinary selectivity for -receptors (K i ␦

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
62
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 21 publications
6
62
1
Order By: Relevance
“…1000 times the original AD 50 . Clearly, our data as well as those of Zhao et al (2002), show that tolerance develops very differently to [Dmt 1 ]DALDA in the spinal cord and brain. In an attempt to understand these differences, we determined the expression of the three major opioid receptor genes and the three major opioid peptide precursors in brain and spinal cord.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…1000 times the original AD 50 . Clearly, our data as well as those of Zhao et al (2002), show that tolerance develops very differently to [Dmt 1 ]DALDA in the spinal cord and brain. In an attempt to understand these differences, we determined the expression of the three major opioid receptor genes and the three major opioid peptide precursors in brain and spinal cord.…”
Section: Discussionsupporting
confidence: 66%
“…Another group reported a somewhat similar study of chronic treatment with [Dmt 1 ]DALDA (Zhao et al, 2002). They also found that tolerance to spinal drug administration was much greater than to i.c.v.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Furthermore, analgesia studies in mice suggest that SS-02 readily penetrates the blood-brain-barrier after subcutaneous administration. 31 This has also been confi rmed by the detection of …”
Section: Protection Against Ischemia-reperfusion Injurymentioning
confidence: 74%